Renegotiations in public-private partnerships: Theory and evidence - Eduardo Engel; Ronald Fischer; Alexander Galetovic (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2014)
Public-private partnerships (PPPs) have the potential to increase efficiency and improve resource allocation. However, contract renegotiations are common and make us question the benefits to PPPs. Under current accounting standards, PPPs allow intertemporal reallocations of infrastructure spending that do not occur under traditional methods of procuring infrastructure and which allow governments to escape the constraints of congressional purview. We review the theoretical results in Engel et al. [2009a] as well as data from Colombia, Chile and Peru, comprising 610 highway PPPs and 540 renegotiations processes to verify these predictions. The data and original analysis comes from Bitran et al. [2013], complemented with additional descriptive statistics. The empirical evidence supports the predictions of the theoretical model.
Keywords: H21; L51; L91; 330; Build-operate-and-transfer; concessions; lowballing